Pregnancy outcomes with confirmed SARS-CoV-2 infection during first wave: a review - Naz Memon, Farah; Naz, Saima; Tayyaba Rahat (Journal of the Pakistan Medical Association, 2022)
Maternal and foetal care has become an important concern in the wake of enormous global spread of coronavirus disease-2019 (COVID-19), but there is scarcity of information about maternal and perinatal outcomes. The current review was conducted from March to July 2020. Appropriate and related databases were searched electronically by using terms, like “COVID-19 and pregnancy”, “pregnancy outcomes of COVID-19”. Pooled analysis of the reviewed studies showed that of the 164 newborns, vertical transmission was noted in 7(2.95%). The most common element 140(84.98%) was caesarean section deliveries. COVID-19 pneumonia developed in almost 54(30.90%) of 175 women. The most common symptom of COVID-19 among women was fever 88(50.77%). Adverse maternal and foetal outcomes were found to be associated with COVID-19 in the form of severe illness, increased rates of caesarean section deliveries and worse birth outcomes. Yet, vertical transmission of COVID-19 infection remains debatable. Key Words: COVID-19, Maternal outcomes, Perinatal outcomes.